Evaluation of certain food additives and contaminants : thirtieth report of the Joint FAO/WHO Expert Committee on Food Additives, meeting held in Rome from 2 to 11 June 1986 - Joint FAO/WHO Expert Committee on Food Additives; Food and Agriculture Organization of the United Nations; World Health Organization (Geneva : World Health Organization, 1987)
Assesses available chemical, biological, and toxicological data for 21 different compounds classified as anti-oxidants, flavouring agent, food colours, sweetening agents, thickening agents, and miscellaneous food additives. Information on these compounds is repeated, in tabular form, in annexes indicating acceptable daily intakes, changes in the status of specifications, the need for further toxicological studies, and the information required from these studies.
1. Introduction -- 2. General considerations -- 3. Comments on specific food additives and contaminants -- 4. Establishment and revision of certain specifications and general methods -- 5. Principles for the safety assessment of food additives and contaminants in food -- 6. Future work -- 7. Recommendations to FAO and WHO -- Annexes
Keywords: Food Additives; Food Contamination; Community Health and Primary Health Care